A vector theory for forward propagation in a structured ionosphere. (April 2021) - Rino, C.L.; Carrano, C.S.
Abstract: The scalar forward propagation equation, most often with the parabolic approximation, has been used extensively for simulating ionospheric radio propagation. More recently, the formalism has been applied at HF frequencies where external magnetic field effects must be accommodated. This paper presents a generalization of the forward propagation equation to accommodate vector fields with forward-marching integration. The ramifications for characteristic mode identification are explored. Highlights: Propagation in inhomogeneous anisotropic media at HF frequencies must accommodate polarization. The scalar forward propagation equation can be generalized to accommodate vector fields. In an inhomogeneous anisotropic medium the vector field realizations must be processed to identify characteristic modes as with actual field measurements.